Vulnérabilité et adaptation des sociétés littorales aux aléas météo-marins entre Guérande et l'île de Ré, France (XIVe - XVIIIe siècle) - Emmanuelle Athimon; Mohamed Maanan; Thierry Sauzeau; Jean-Luc Sarrazin (VertigO, 2016)
The space-time frame of the study is located in France, from the Guérande peninsula to the island of Ré, between the fourteenth and the eighteenth century. Sensitive and brittle, this area is regularly battered by violent winds. It also undergoes episodic sea flooding that can cause ruptures of balance. This research offers to query the notion of social and territorial vulnerability to the crises caused by exceptional events in history. On this purpose, we firstly examined and identified the hazards. The choice was made to mainly focus on those related to the wind (storms) and the sea (coastal flooding). We then studied the impacts of these phenomena on medieval and modern coastal societies and analyzed their perceptions and reactions. This approach allowed to simultaneously address and consider the vulnerability and the adaptability of ancient coastal populations, especially through the memory storage process, the risk awareness, the development of prevention, etc. Thinking the concept of vulnerability in a long time consideration forces the historian to position himself at the crossroads between natural factors, mental perceptions, territory management and political decisions.